Improving Sales Force Performance Through Effective Human Resource Management - Indri Astuti; Hadi Purnomo; Nurwulan Kusuma Devi; Prihatina Jati (Return : Study of Management, Economic and Bussines, 2023)
Human resources (HR) is one of the important things in supporting the achievement of a maximum goal. The company as a profit-oriented organization really expects targets in terms of sales, production, delivery, performance and other goals within the company to be achieved immediately. This study used a qualitative method of collecting data sourced from documents, books, journals, articles / other online media, using grounded research theory aimed at developing theory (theory building) inductively based on data. The result of this study is that human resource management can improve sales force performance. Through the results of Suparman's research that human resource management is able to improve sales force performance in the case example here is PT. Perdana Mitra Abadi Cianjur which develops the potential of its employees through the development of human resource management, namely providing in-service training to its employees regarding product knowledge and soft skills.